Prevalence and correlates of antibodies to Neospora caninum in dogs in Portugal - Maia Carla; Cortes Helder; Brancal Hugo; Lopes Ana Patrícia; Pimenta Paulo; Campino Lenea; Cardoso Luís (Parasite, 2014)
Neosporosis, caused by Neospora caninum, is an important cause of abortion in cattle and of neurological disease in dogs. This study investigated the prevalence and correlates of antibodies to N. caninum in 441 dogs from the five regions of mainland Portugal. A commercial competitive enzyme-linked immunosorbent assay (cELISA) was used and specific antibodies were detected in 35 (7.9%) dogs. Seroprevalence levels were significantly different among some of the studied regions, as well as between stray dogs (13.6%) and hunting dogs (1.7%). The difference between seropositivity in dogs presenting musculoskeletal or neurological signs (21.4%) and that in animals without clinical signs compatible with neosporosis (5.6%) was close to statistical significance. This is the first report on the seroprevalence of N. caninum in dogs in Portugal. Neosporosis should be considered in the differential diagnosis of neurological disorders of dogs.